Development of Performance Assessment Instrument for Nurses Based on Web in Inpatient Unit - Aprilia Nuryanti; Nursalam Nursalam; Mira Triharini (Universitas Airlangga, 2017)
Introduction: Performance assessment instrument will be problematic when it is not representative in describing the competency because it is not obvious indicators and inappropriate performance standard to nursing’s task. The purpose of this study is to develop nurses’ performance assessment instrument based on the web from multi sources assessment inpatient unit at SMC Hospital.Methods: This study had two phases. The first phase was an explanatory overview of the performance assessment system using questionnaires completed by 53 respondents of nurses, selected by purposive sampling. Instrument development based on FGD with six decision makers in the hospital. Validity was tested by Pearson Product Moment Correlation and reliability of instrument’s was tested by alpha Cronbach. The second phase was socialization and instrument test to observe the quality of instrument using a questionnaire by 47 respondents and recommendations made by 8 participants of FGD. The samples were selected by purposive sampling technique. Performance assessment system was moderate at 58.49%. All questions which aimed to measure the performance of nurses were valid and reliable. The quality of nurses’ performance assessment instruments based on the web was a good category, which was functionality: 81.60; reliability: 78.16; efficiency: 80.85; usability: 81.70 and portability: 81.70.Results: The result was a web-based assessment format, scoring with Likert scale, resource assessment by the direct supervisor which was a multisource evaluator, the development of performance graph, and confidentiality of data on the database server.Discussion: Recommendations for hospital is to make policy based on the final value of the performance assessment by the supervisor which was multisource feedback and it needs a global writing on a form of performance assessment result.